МАКТАБГАЧА ТАЪЛИМ ПСИХОЛОГИК ХИЗМАТИНИНГ АМАЛДАГИ МОДЕЛИ - Турғунов, А.А. (SCIENCE and SOCIETY, 2020)
The article describes the modern model and strategy of the psychological service of preschool education. Information is provided about the activities of a teacher-psychologist in the psychological service of preschool education, their duties, responsibilities, opportunities, and shortcomings in its organization.
Keywords: preschool educational institution; psychologist; model of psychological service; preschool children; model; strategy; activities; functional task; diagnostics; correction; “emergency care”